Player’s Physical Fitness, Training Process, and Team Support Impact on Football Team Performance in Thailand: Mediating Role of Player Satisfaction - Mochammad Fahlevi; Kittisak Jermsittiparsert; Navaporn Wongsuwan; Mohammed Aljuaid; Khunanan Sukpasjaroen; Thitinan Chankoson (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Globally, team performance has become a crucial factor for the success of any sport, attracting the interest of regulators, coaches, and new researchers. Therefore, the current study investigates the impact of critical factors such as physical fitness, training process, and team support on the performance of the Thai national football team. In addition, this article examines the mediating effect of player satisfaction on the relationships between physical fitness, training process, team support, and football team performance in Thailand. The researchers collected the data using primary data collection methods such as questionnaires. The respondents were selected using purposive sampling, and smart-PLS was used to assess the reliability and relationships between variables. The results demonstrated that physical fitness, training process, and team support positively affect the performance of the Thai national football team. In addition, the results indicated that player satisfaction significantly mediates the relationships between physical fitness, training process, team support, and football team performance in Thailand. This article assists regulators in developing regulations regarding team performance and serves as a guide for future researchers investigating this field.